Let history judge : the origins and consequences of Stalinism - Roy A. Medvedev ; translated by Colleen Taylor, edited by David Joravsky, and by Georges Haupt. (Knopf, 1971)
Translation of K sudu istorii. Includes bibliographical references and index.